2018
DOI: 10.3390/su10072468
|View full text |Cite
|
Sign up to set email alerts
|

Research on a Gas Index Reflecting the Sorption Process on Carbon Materials in Coal Mines

Abstract: Based on the concentration of gases such as propylene and ethylene in the atmosphere of a mine, it is possible to assess the development of a mine fire. With the increase of coal temperature, an increased emission of these gases has been observed. However, the experiment results presented in this paper prove that the use of propylene and ethylene for the prediction of the spontaneous combustion of coal have some limitations. It was found that during a flow of gas mixture through the sorption column, propylene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
(23 reference statements)
1
4
0
Order By: Relevance
“…It was found that the analyzed samples reached the values of the ratio of ethylene to propylene concentration in the range of 2–3. A similar relationship between the gases can be found in the work 33 . In the measurement series with a different particle size of coal in a fixed–bed (Fig.…”
Section: Methodssupporting
confidence: 79%
See 1 more Smart Citation
“…It was found that the analyzed samples reached the values of the ratio of ethylene to propylene concentration in the range of 2–3. A similar relationship between the gases can be found in the work 33 . In the measurement series with a different particle size of coal in a fixed–bed (Fig.…”
Section: Methodssupporting
confidence: 79%
“…It can be assumed that the increasing propylene concentration in the mixture caused an increase in the driving force and a decrease in the number of active places available for ethylene adsorption because propylene has a better sorption ability as compared to ethylene. The differences between hydrocarbons properties were discussed in more detail in the works 22,25,33 . The higher reactivity of propylene can be connected with higher critical temperature and more stable secondary carbocation which is formed from propylene during the addition reaction 16,49 .…”
Section: Resultsmentioning
confidence: 99%
“…Coal samples obtained from the Upper Silesia Coal Basin, Poland, according to the Polish National Standard: PNG‐04502:2014‐1 were crushed, ground, and sieved into three different fractions with sizes at the range of 0.25 to 0.50, 0.70 to 1.00, and 1.00 to 2.00 mm. The reason for choosing the above particle sizes for the coal samples examined in the sorption experiment is that according to the field literature, the sorption tests have been previously performed only for coal of grain size from 0.5 to 0.7 mm. The characteristic of the samples tested is presented in Table .…”
Section: Experimental Facilitymentioning
confidence: 99%
“…So the size and availability of the surface area have a great influence on the amount of sorbed gases. The smaller the grain size of coal is, the larger the surface area, the number of active sites, and, consequently, the amount of the sorbed gases . Therefore, the places in the coal mine where finer grains of coal can be accumulated are the most dangerous sites in which the sorption processes can take place.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation